(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Objective: This study evaluated the effects of combined ethanol extract of Anthocleista vogelii and Alstonia boonei (CEAA) stem barks on the liver function indices of benign prostatic hyperplasia (BPH)-induced rats. Materials and Methods: Thirty (30) male Wistar rats were randomly grouped into five groups (n = 6). BPH was induced subcutaneously with 5 mg/kg/day of testosterone propionate in olive oil. Groups 1-3 served as normal, BPH control (untreated) and standard drug control respectively, while Groups 4 and 5 were BPH-induced rats and treated with 200 and 400 mg/kg/day of the CEAA respectively after one hour of the BPH induction. After twenty-eight days of treatments, biochemical and histopathological analyses were conducted using standard analytical procedures. Results: The acute toxicity result of CEAA indicated no mortality or adverse reactions. Significant body weight change was only observed in the first week from the group-administered 200 mg/kg/day of CEAA. Liver damage was evident in the BPH control characterized by significant (P<0.05) increase in relative liver weight and liver enzymes’ (AST, ALT, ALP) activities but a reduction in total protein and globulin levels. Treatment with CEAA attenuated the liver damage by significantly (P<0.05) reducing the elevated relative liver weight and liver enzyme function activities and elevated total protein and globulin levels. Conclusion: The revealed that the combined ethanol extract of Anthocleista vogelii and Alstonia boonei (CEAA) stem barks possess hepatoprotective effects that could improve liver integrity and functions in BPH induced rats.